Study on the anti-inflammatory activity of Polyscias scutellaria (Burm. f.) Fosberg leaves extract and its phytochemical components - Alfian Syarifuddin, Arief Nurrochmad, Nanang Fakhrudin (Journal of Applied Pharmaceutical Science, 2025)
Polyscias scutellaria (Burm.f) Fosberg has traditionally been used to treat various diseases. However, the study of its in vivo anti-inflammatory effects, mechanism of action, and metabolite profile is limited. This study aimed to investigate the free radical scavenging activity and the anti-inflammatory property of P. scutellaria leaves extract and study its mechanism of action on pro-inflammatory cytokines [tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6)]. The leaves of P. scutellaria were macerated in ethanol (90%) to yield ethanol extract of P. scutellaria leaves (EEPS). The rats were divided into 5 groups (n = 5): solvent group, sodium diclofenac group (13.65 mg/kg), and EEPS at the dose of 100, 200, and 400 mg/kg). The rats were pretreated with EEPS and the oedema were induced by carrageenan (1%). The oedema volume (inflammation) was measured and the expression of pro-inflammatory cytokines was assessed using an enzyme-linked immunosorbent assay. In addition, the chemical constituent of EEPS was analyzed using liquid chromatography-orbitrap high-resolution mass spectrometry (LC-HRMS). EEPS at doses of 200 and 400 mg/kg inhibited inflammation in carrageenan-induced rat paw oedema. The same effect was also observed in rats treated with sodium diclofenac. EEPS also significantly decreased the levels of TNF-α and IL-1β, but not IL-6. Phytochemical analysis using LC-HRMS revealed that the extract contains known antioxidant or anti-inflammatory compounds, such as ursolic acid and chlorogenic acid. EEPS demonstrated anti-inflammatory activity in carrageenan-induced paw oedema by suppressing the level of pro-inflammatory cytokines TNF-α and IL-1β.
Keywords: Polyscias scutellaria, herbal medicine, inflammation, mass spectroscopy, TNF-α, IL-1β, IL-6